Putusan MK Terkait Presidential Threshold Menuju Demokrasi yang Lebih Inklusif Atau Tantangan Baru falam Pemilu - Novita Novita; Moh. Syuhada Ramdhani; Novi Andini (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research analyzes the Constitutional Court Decision Number 62/PPU-XXII/2024 regarding the constitutionality of the presidential threshold and its implications for the development of inclusive democracy in Indonesia. Using a juridical-normative and conceptual approach, this study examines the presidential threshold provisions as regulated in Article 222 of Law Number 7 of 2017 on General Elections from the perspective of inclusive democracy theory and electoral systems. The results show that the Constitutional Court affirmed the constitutionality of the presidential threshold as an open legal policy of the legislators, while also noting that lawmakers should reconsider the threshold percentage in future revisions of the Election Law. This research identifies a tension between two equally important democratic values: government effectiveness and political representation. On one hand, the presidential threshold can strengthen the presidential system by encouraging political party consolidation and creating more stable governance. On the other hand, this provision potentially limits political inclusivity by reducing the diversity of choices for voters and restricting opportunities for small or new political parties to nominate presidential and vice-presidential candidates independently. This study concludes that to realize a more inclusive democracy following the Constitutional Court Decision, further efforts are needed to reform the electoral system, strengthen political parties, enhance political education, and develop innovations in political participation.